A Review of Research Paper: Developing Character Education-Based English Teaching Materials for Elementary School - Maulina, Riskiati; Jamilah, Jamilah (EDUPEDIA Publisher, 2024)
Character education should be prioritized in education not only for students of higher education but for all, including elementary school students. One of the ways is integrating it in subject materials, including English teaching materials. The current study contends that literature can be used as a medium to build students' characteristics by undertaking a comprehensive review of relevant sources. This study used library research where the data sources are credible authorized national periodicals. This study shows that there are some points should be considered in developing English teaching materials, such as: a) teachers need to consider the students’ needs; b) teachers need to make it integrated with character education as demand and needs; c) teachers need to involve planning, developing, evaluating, and revising the product made in the form of teaching materials